2017
DOI: 10.1039/c7ra01070b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in vitro leishmanicidal activity of novel [1,2,3]triazolo[1,5-a]pyridine salts

Abstract: Leishmaniasis remains a significant worldwide problem; it is of great interest to develop new drugs to fight this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Finally, it is noted that pyridotriazoles have so far received little attention in fields such as medicinal chemistry where nitrogen‐based heterocycles traditionally play dominating roles for example, as privileged scaffolds in drug discovery. A couple of studies suggest that some molecules bearing pyridotriazole structure show antileishmanial activity, and several shown to be efficient DNA photocleavage agents with potential applications in phototherapy [103–106] . There is no doubt that further development in these areas will offer many opportunities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is noted that pyridotriazoles have so far received little attention in fields such as medicinal chemistry where nitrogen‐based heterocycles traditionally play dominating roles for example, as privileged scaffolds in drug discovery. A couple of studies suggest that some molecules bearing pyridotriazole structure show antileishmanial activity, and several shown to be efficient DNA photocleavage agents with potential applications in phototherapy [103–106] . There is no doubt that further development in these areas will offer many opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies suggest that some molecules bearing pyridotriazole structure show antileishmanial activity, and several shown to be efficient DNA photocleavage agents with potential applications in phototherapy. [103][104][105][106] There is no doubt that further development in these areas will offer many opportunities. The chemistry of pyridotriazoles is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…The activities were better than that of the control drug Glucantime, with IC 50 values of 18.0–25.6 μM and 18.4–30.4 μM, respectively. The selectivity index (SI > 56) of compound 40 was higher than the control drug Glucantime (SI < 1) [ 46 ].…”
Section: Antileishmanial Activities Of 123-triazolium Saltsmentioning
confidence: 99%
“…Studies have shown that the triazolium transformated from triazole have good bioactivities [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Molecules containing 1,2,3-triazolium units have been proven to exhibit a variety of biological activities, including antibacterial [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], antifungal [ 5 , 6 , 7 , 8 , 9 , 35 ], anticancer [ 10 , 11 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and antileishmanial [ 12 , 43 , 44 , 45 , 46 ] properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinically relevant form of the parasite is the amastigote form, which shows metabolic differences from the extracellular forms, promastigotes can be used for fast screenings of potential compounds (Tempone et al 2005;Martín-Montes et al 2017;Silva et al 2017). Thus, in this study, we evaluated the effect of dihydroquinoline lactone derivatives against promastigote forms of L. (L.) amazonesis in vitro.…”
Section: Antileishmanicidal Activitiesmentioning
confidence: 99%